From Waste to Value: Optimization of Ultrasound-Assisted Extraction of Anthocyanins and Flavonols from Pistacia lentiscus L. Oilcakes - Lucrezia Muti; Luana Beatriz dos Santos Nascimento; Giulia Goracci; Cassandra Detti; Cecilia Brunetti; Anna Rita Bilia; Francesco Ferrini; Antonella Gori (Molecules)
Pistacia lentiscus L., commonly known as the mastic tree or lentisk, is a woody Mediterranean plant revered for its ecological relevance as well as for its extensive ethnobotanical heritage. Historically, the fruits and the resin of P. lentiscus have been widely utilized in traditional medicine, underscoring its important role in local healing practices. Given these properties, this study explored an innovative approach to efficiently extract anthocyanins and flavonols from P. lentiscus oilcakes utilizing ultrasound-assisted extraction (UAE) as an alternative to conventional solvent extraction. Liquid chromatography–mass spectrometry (LC-MS) and high-performance liquid chromatography with diode-array detection (HPLC-DAD) were used to identify and quantify the anthocyanins and flavonols, revealing the successful extraction of eight distinct anthocyanins and twenty flavonols. A Fractional Factorial Design (FFD) followed by a Box–Behnken design (BBD) were applied to optimize the yield of anthocyanins and flavonols. The optimal extraction conditions found were to be an extraction time of 15 min with 70% ethanol as the solvent and a liquid-to-solid ratio of 0.012 L g−1, which resulted in a maximum extraction yield of 19.78 mg g−1 dry extract for the Total Flavonol Content and over 25.4 mg g−1 dry extract for the Total Flavonol and Anthocyanin Content. By elucidating the optimal conditions for extracting anthocyanins and flavonol glycosides, this study opens promising avenues for utilizing P. lentiscus oilcake by-products, supporting sustainable practices, and advancing the valorization of Mediterranean bio-resources for health-promoting applications.